(untitled) (Al-Farooq Journal of Sciences, 2026)
The aim of this study was to identify the phenomenon of cyber blackmail and its impact on the mental health of a sample of adolescent girls in the city of Tripoli, and to understand the types and methods of blackmail in Libyan society in order to mitigate the psychological effects suffered by many adolescent girls, such as anxiety, depression, and various other mental disorders. This research followed the descriptive-analytical approach. To achieve its objectives and answer its hypotheses, the researcher prepared a questionnaire to measure the prevalence of the cyber blackmail phenomenon and assess its impact on mental health. The questionnaire was administered to a sample consisting of (100) adolescent girls. The data obtained from them was then entered and statistically analyzed using the Statistical Package for the Social Sciences (SPSS) program. The study concluded with several results indicating a high level of psychological disorders resulting from the prevalence of cyber blackmail practiced against many girls, as it contributes significantly to increasing psychological problems such as anxiety and depression. Recommendations were proposed, including: providing confidential psychological counseling services for adolescent girls who are victims of blackmail, and incorporating the topic of cybersecurity into school curricula. Suggestions included: examining differences in mental health between adolescent girls exposed and not exposed to cyber blackmail in the city of Tripoli